2018
DOI: 10.18805/ajdfr.dr-1389
|View full text |Cite
|
Sign up to set email alerts
|

Whey Proteins: A potential ingredient for food industry- A review

Abstract: Whey, a byproduct of cheese and whey manufacturing was considered as waste of dairy industry. There has been a continuous increase in dry whey production due to advances in processing technologies such as ultra filtration, reverse osmosis and nanofiltration process. High value whey based ingredients has received much more attention in food industry due to its exceptional functional and nutritional properties. It is an important source of bioactive peptides, essential amino acids, b-Lactoglobulin, Lactalbumin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…The WP then unfold at the interface with hydrophilic and hydrophobic groups toward the liquid and air phase, respectively, and form highly viscoelastic interfacial film that stabilizes the air bubbles (Xiong et al, 2020). Similar to foaming, the role of WP in emulsification is to provide an interfacial membrane around the lipid globule to prevent creaming, coalescence, flocculation, and oiling off (Kumar et al, 2018). The gelation of WP starts with the initial unfolding of a WP molecule followed by subsequent aggregation either by addition of salt or decreasing the pH (Kharlamova et al, 2018).…”
Section: Whey Protein As Food Additivementioning
confidence: 99%
See 3 more Smart Citations
“…The WP then unfold at the interface with hydrophilic and hydrophobic groups toward the liquid and air phase, respectively, and form highly viscoelastic interfacial film that stabilizes the air bubbles (Xiong et al, 2020). Similar to foaming, the role of WP in emulsification is to provide an interfacial membrane around the lipid globule to prevent creaming, coalescence, flocculation, and oiling off (Kumar et al, 2018). The gelation of WP starts with the initial unfolding of a WP molecule followed by subsequent aggregation either by addition of salt or decreasing the pH (Kharlamova et al, 2018).…”
Section: Whey Protein As Food Additivementioning
confidence: 99%
“…WP could also replace other animal proteins to stabilize the meat products. A study showed that meatless patties containing textured WP with mushroom and vegetable flavor had similar acceptability as commercial soya patty (Kumar et al, 2018). Concentrations of WP exceeding 50% can create products with functional properties that are helpful as a fat replacer in low fat ice cream (Akbari et al, 2019).…”
Section: Whey Protein As Food Additivementioning
confidence: 99%
See 2 more Smart Citations
“…The main ingredient of the described formula is whey protein concentrate (WPC80). It is a rich source of amino acids and contains a high concentration of essential amino acids [ 5 ]. Additionally, another ingredient of the described formula, acid casein, has water-binding properties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%